Effects of diesel and bio-diesel oils temperature on spray and performance of a diesel engine - Ekkachai Sutheerasak (KKU Engineering Journal, 2014)
Research paper is the spray and engine performance investigation from preheated diesel and biodiesel oils at fuel temperature from 60 to 90 o C by comparing with non-preheated oil. In the experiment, there are fuel injection modeling and diesel engine testing, which is direct injection, 4 stroke and 4 cylinders. Results of fuel spray show that preheated diesel oil increase 4.7degree of spray angle and decrease 4.30 % of fuel injection pressure, as preheated bio-diesel oil increase 7.6degree of spray angle and decrease 13.90 % of fuel injection pressure to compare with non-preheated oil. As engine preformance testing results, preheated diesel oil increase 26.20% of thermal efficiency and decrease 4.30 % of BSFC, as preheated bio-diesel oil increase 30% of thermal efficiency and decrease 29.90 % of BSFC to compare with non-preheated oil.